Altitudinal Distribution of Meltwater and Its Effects on Glacio‐Hydrology in Glacierized Catchments, Central Asia. (21st November 2019) - Shafeeque, Muhammad; Luo, Yi; Wang, Xiaolei; Sun, Lin
Abstract: In glacierized catchments, elevation is correlated with meltwater through its association with temperature, precipitation, and glacier hypsometry. The revelation of the altitudinal distribution of meltwater, unattended and not fully understood in previous work, might provide a better understanding of climate change impacts on glacio‐hydrology. Here, critical zone approach was defined and applied in 12 glacierized catchments of the Tien Shan–Pamir–Karakorum Mountains, Central Asia using manually calibrated glacier‐enhanced Soil and Water Assessment Tool model over 1966–2005. The critical zone, a sequence of elevation bands with above‐average snow and glacier melt, contributes maximum meltwater to total runoff. The critical zone shared 37%–95% (average = 80%) of meltwater contributions to total runoff, although its size was only 13%–30% of the total elevational relief. The critical zone controlled 76% and 82% variability in relative changes of glacier area and total runoff at the catchment scale, respectively. The increase in temperature was identified as the dominant driver for variations in total runoff in all catchments except Vakhsh and Yurungkash, where precipitation change remained dominant. Overall, glacier hypsometry limited the first‐order control of meltwater distributions on glacio‐hydrology. It is concluded that critical zone approach can interpret the proxy role of elevation to affect water availability under climate and glacier area change in glacierized catchments. Abstract : Research Impact Statement : Critical zone controls larger portion of variability in meltwater and runoff, whereas temperature change is identified as dominant driver for total runoff changes in most of the glacierized catchments.